2011
DOI: 10.1021/ie200344t
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scalable and Comprehensive Infrastructure Model for Carbon Dioxide Utilization and Disposal

Abstract: Much of the previous research on carbon capture and storage (CCS) has focused on individual technologies for disposing of CO 2 , such as capture, storage, sequestration, or transport. Moreover, recent research work considers utilization of CO 2 as fuels, chemicals, or nutrients for bioreactors. To efficiently manage CO 2 and the economic benefits achieved by this process, the CO 2 transport and processing infrastructure supporting CCS will have to be constructed at a macro-scale. This paper introduces a scalab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 17 publications
0
45
1
1
Order By: Relevance
“…Huang et al [144] (d = 143) provided a general review of optimisation methods used for the deployment of CCS power plants, such as energy expansion planning optimisation models, pipeline network planning, source-sink optimisation models, or CO 2 sequestration optimisation models. Other key papers included Han et al [145] (d = 103), who developed a scalable and comprehensive infrastructure model that generates an integrated, profit-maximising CCS system from capture to storage of CO 2 ; Zhang et al [146] (d = 99), who provided a mixed integer linear programming (MILP) model for the design of integrated carbon capture, transport, and storage infrastructure using the example of Qatar; Zhang et al [147] (d = 95), who developed an inexact management model (ICSM) to identify optimal strategies to plan CO 2 capture and sequestration under uncertainty; and Lee et al [148] (d = 86), who proposed a multi-objective MILP model combined with a life cycle assessment model in order to optimise both cost and environmental impacts.…”
Section: Cluster C5 (Pink 255 Nodes 6%)-the Chemistry Of Capture Anmentioning
confidence: 99%
“…Huang et al [144] (d = 143) provided a general review of optimisation methods used for the deployment of CCS power plants, such as energy expansion planning optimisation models, pipeline network planning, source-sink optimisation models, or CO 2 sequestration optimisation models. Other key papers included Han et al [145] (d = 103), who developed a scalable and comprehensive infrastructure model that generates an integrated, profit-maximising CCS system from capture to storage of CO 2 ; Zhang et al [146] (d = 99), who provided a mixed integer linear programming (MILP) model for the design of integrated carbon capture, transport, and storage infrastructure using the example of Qatar; Zhang et al [147] (d = 95), who developed an inexact management model (ICSM) to identify optimal strategies to plan CO 2 capture and sequestration under uncertainty; and Lee et al [148] (d = 86), who proposed a multi-objective MILP model combined with a life cycle assessment model in order to optimise both cost and environmental impacts.…”
Section: Cluster C5 (Pink 255 Nodes 6%)-the Chemistry Of Capture Anmentioning
confidence: 99%
“…For instance, analyzing the NATCARB data (National Energy Technology and Laboratory, 2010a), we have screened 161 CO 2 -EOR sites as potential utilization locations ( Finally, while studies (Odenberger et al, 2008;Kjärstad et al, 2011;Mikunda et al, 2011;Klokk et al, 2010;Strachan et al, 2011;Bakken et al, 2008;Middleton and Bielicki, 2009b;Middleton et al, 2012;Kuby et al, 2011;Han and Lee, 2011;Han et al, 2012;Tan et al, 2012;van den Broek et al, 2008;Zheng et al, 2010;Johnson and Ogden, 2011;Figueroa et al, 2008) addressed regional CO 2 capture and sequestration and CO 2 pipeline networks (Morbee Fig. 5.…”
Section: Ccus and Ccu Challengesmentioning
confidence: 99%
“…van den Broek et al once applied hubespoke models to study the optimal design of pipeline network for CO 2 transport in the Netherlands (van den Broek et al, 2010). Han and I. Lee once applied hube spoke models to optimally design CO 2 pipeline networks in eastern South Korea simultaneously, including pipeline, tanker truck, tanker ship, and tanker rail car (Han and Lee, 2011). Apart from sequestrating CO 2 into geological formations underground, captured CO 2 is also utilized to produce biobutanol and green polymers (Han and Lee, 2011).…”
Section: Previous Studies On Models For Ccs Pipeline Network Designmentioning
confidence: 99%
“…Han and I. Lee once applied hube spoke models to optimally design CO 2 pipeline networks in eastern South Korea simultaneously, including pipeline, tanker truck, tanker ship, and tanker rail car (Han and Lee, 2011). Apart from sequestrating CO 2 into geological formations underground, captured CO 2 is also utilized to produce biobutanol and green polymers (Han and Lee, 2011). Pöyry Energy Consulting once applied hubespoke models to study CO 2 pipeline networks in the United Kingdom, and the design result is shown in Figure 9.9 (Hare and Ladbrook, 2007).…”
Section: Previous Studies On Models For Ccs Pipeline Network Designmentioning
confidence: 99%